Determination of Ascorbic Acid by a Gold–Zinc Oxide Nanoparticle-Modified Glassy Carbon Electrode. (21st September 2016) - Zhang, Yanli; Liu, Hongjun; Li, Haizhen; Chen, Meng; Pang, Pengfei; Wang, Hongbin; Wu, Zhan; Yang, Wenrong
ABSTRACT: A novel electrochemical sensing platform was developed based on flower-like gold–zinc oxide core–shell nanoparticles and a graphene nanocomposite-modified glassy carbon electrode. The gold–zinc oxide core–shell nanoflowers were synthesized by seed growth and characterized by high-resolution transmission electron microscopy, energy-dispersive X-ray spectroscopy, and ultraviolet-visible absorption spectroscopy. The modified electrode provided good electrocatalytic properties, rapid response, high stability, and favorable reproducibility for determination of ascorbic acid. The performance of the sensor included a linear dynamic range from 1.0 × 10 −7 to 6.0 × 10 −4  M, a limit of detection of 3.9 × 10 −8  M, and a sensitivity of 24.12 µA/mM. The nanocomposite also provided excellent selectivity and lower potential for the oxidation of ascorbic acid. The sensor was used for the determination of ascorbic acid in tablets with satisfactory results. This device provides rapid, simple, and selective determination of ascorbic acid.